Pendekatan alternatif dalam menghasilkan stability lobes diagram untuk memprediksi getaran chatter pada proses pemesinan berdinding tipis - Agus Susanto (LPPM ITK, 2021)
Machining is widely used for finishing process of the entire manufacturing process chain. Machining process of thin plate, however, is not an easy task. This is because excessive vibration (chatter) can rise during operation. To predict the chatter vibration, a stability lobe diagram (SLD) is usually utilized which is strongly dependent on the frequency response function (FRF). This paper proposes an alternative approach for analyzing modal analysis by finite element method (FEM) to obtain FRF during machining thin-walled plate. The result showed that simulation result has good enough agreement to experimental result with slight differences caused by the assumed boundary conditions in the FEM process. This approach can be used to reduce the use of hammering tests and can be used to get FRF of multi stage working.